1980
DOI: 10.1111/j.1399-3054.1980.tb03269.x
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic activities of cadmium‐treated tomato plants

Abstract: Tomato plants (Lycopersicum esculentum Mill. cv. Moneymaker) grown on nutrient medium containing cadmium exhibit reduced net photosynthesis and reduced contents of chlorophyll and accessory pigments. In chloroplasts isolated from cadmiumtreated plants photosystem II activity, as measured by 2,6-dichlorophenolindophenol photoreduction, and photosystem II -(-I activity (H2O -> methyl viologen) were both inhibited to about 60%, When 1,5-diphenylcarbazide was used as artificial electron donor, no significant cadmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
109
2
5

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(130 citation statements)
references
References 19 publications
14
109
2
5
Order By: Relevance
“…Most experiments performed in vitro have shown interference by Cd# + on photosystem II (PSII) activity, which is especially sensitive to this metal. Inhibition of PSII electron transport is accompanied by the disappearance of granal stacks, the decrease and degradation of membrane acyl lipids (Baszynski et al, 1980), the release of some polypeptides associated with the oxygen-evolving complex, and the disorganization of the light-harvesting complex II (LHCII) antenna system (Krupa, 1988). On the other hand, it has been shown that Cd# + also affects photosynthesis by inhibiting different reaction steps in the Calvin cycle (Weigel, 1985 ;Siedlecka & Krupa, 1996).…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation
“…Most experiments performed in vitro have shown interference by Cd# + on photosystem II (PSII) activity, which is especially sensitive to this metal. Inhibition of PSII electron transport is accompanied by the disappearance of granal stacks, the decrease and degradation of membrane acyl lipids (Baszynski et al, 1980), the release of some polypeptides associated with the oxygen-evolving complex, and the disorganization of the light-harvesting complex II (LHCII) antenna system (Krupa, 1988). On the other hand, it has been shown that Cd# + also affects photosynthesis by inhibiting different reaction steps in the Calvin cycle (Weigel, 1985 ;Siedlecka & Krupa, 1996).…”
Section: mentioning
confidence: 99%
“…(Baszynski et al, 1980 ;Baszynski, 1986 ;Van Assche et al, 1988 ;Van Assche & Clijsters, 1990). In particular, Cd# + causes structural changes in chloroplasts (Becerril et al, 1988) and inhibits chlorophyll (Chl) biosynthesis (Stobart et al, 1985 ;Van Assche & Clijsters, 1990 ;Somashekaraiah et al, 1992).…”
Section: mentioning
confidence: 99%
“…Nevertheless, under an adequate Mn supply, Cd-treated white lupins showed a greater Cd net uptake and accumulation, although this proved not to be toxic; the plants therefore showed a certain Cd tolerance. Reducing the Mn supply to the plants promoted a reduction in Cd uptake, although the opposite has been reported by other authors (Baszynski et al, 1980;Pal'ove-Balang et al, 2006). Plant cells activate different detoxification mechanisms to avoid Cd stress, such as binding the Cd by phytochelatins, accumulating it in cell organelles, immobilising it in cell walls, and the synthesis of stress proteins (Sanità di Toppi and Gabbrielli, 1999).…”
Section: Discussionmentioning
confidence: 94%
“…However, the effects of Mn starvation reducing Cd uptake and plant concentrations should be noted, indicating that this Mn-Cd interaction was not owed to true cation antagonism. Further, Cd, Cu, Fe, Zn and possibly Mn share a common transport site or process in Cd-treated soybean (Cataldo et al, 1983), tomato (Baszynski et al, 1980) and Phytolacca americana L. (a Mn-Cd hyperaccumulator) (Peng et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A higher Mn accumulation in chloroplast when Cd is present in the growth medium was also found in lettuce (Lactuca sativa L., Ramos et al 2002). Moreover, the partial restoration of chloroplast structure damaged by Cd treatment was found after addition of Mn (Baszyński et al 1980). The nitrogen nutrition is one of the most important metabolic processes in plants.…”
mentioning
confidence: 88%